ISOLATION AND IDENTIFICATION OF ESCHERICHIA COLI O157:H7 IN CATTLE STOOL AT PETANG SUBDISTRICT, BADUNG REGENCY-BALI - Suardana, I Wayan; Putri, Putu Januari Ratna Apsari; Besung, I Nengah Kerta (Buletin Veteriner Udayana, 2016)
Coliform are commonly found in livestock stool, including cattles and Escherichia coli (E. coli) is one of the most popular of Coliform groups. Various strains of E. coli are pathogenic which oneof them is serotype O157:H7 which known  producing Shiga like toxin.  The study initiated by collecting 58 samples of fresh cattle stool which were taken from seven villages in the district of Petang, followed by isolating  and identificating of strain. The results of study presented indescriptive and the relationship between each vaiable was analyzed by Spearman 's rho and McNemar test. Among 58 samples, all of them were positive Coliform (100 %), and 29 samples positive E. coli (50 %). Among E. coli positive, that were found  7 samples were positive E. coli O157 ( 12.07% ) and 5 samples positive E. coli O157:H7 (8.62 %). The total Coliform and the number of  E. coliwere highly significant difference, while the number of E. coli O157 and  E. coli O157:H7 were not significant difference. Coliform bacteria in the stool of cattle could not be used as a predictable factor for the presence of  E. coli, E. coli O157 and E. coli O157:H7, but the presence of  E. coli would be enable to predict the presence of E. coli O157 as well as E. coli O157:H7. Futhermore,  the study also showed the presence of E. coli O157 was as a good predictor to the presence of zoonotic agents E. coli O157:H7.
Keywords: cattle stool; Coliform; E. coli; E. coli O157; E. coli O157 : H7